Factors Affecting the Timeliness of Company Financial Reporting - Sih, Agnes Cahyaning; T., Sutrisno (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the factors (managerial ownership, public ownership, company size, company age, and auditor quality) affecting the financial reporting timeliness of companies listed on the Indonesia Stock Exchange during the 2020-2021 period The population of this study includes 724 companies listed on the Indonesia Stock Exchange between 2020 and 2021, from which samples of 587 companies according to the criteria are selected through purposive sampling. This study uses the logistic regression analysis method. Model testing in this study uses the Statistical Package for the Social Sciences (SPSS) version 27 data processing tool. The results of this study suggest that company size has a positive effect on the timeliness of financial reporting. Auditor quality has a positive effect on the timeliness of financial reporting. Public ownership has a negative effect on the timeliness of financial reporting. Managerial ownership has no effect on the timeliness of financial reporting. Company age has no effect on the timeliness of financial reporting.